Industry 4.0 – The Evolution of Business Models - Kainer, Leonard (2017)
Business models need to change over time if companies want to sustain their value creation and value capture. Examples such as Kodak and Nokia, which have failed in digitisation, have shown that companies need dynamic capability incorporating the adaption and renewal of their business models to stay competitive. German companies, especially those forming the backbone of the German economy – small- and medium-sized enterprises (SME) – are confronted by more volatile as well as competitive markets and suffer as a result of pressure from abroad. According to a large number of scientific authors and all types of consultancies, SMEs need to adapt their digitisation strategies to stay competitive in future.